Photocatalytic Acceptorless Alkane Dehydrogenation: Scope, Mechanism, and Conquering Deactivation with Carbon Dioxide. Issue 2 (24th October 2014) - Chowdhury, Abhishek Dutta; Julis, Jennifer; Grabow, Kathleen; Hannebauer, Bernd; Bentrup, Ursula; Adam, Martin; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract Alkane dehydrogenation is of special interest for basic science but also offers interesting opportunities for industry. The existing dehydrogenation methodologies make use of heterogeneous catalysts, which suffer from harsh reaction conditions and a lack of selectivity, whereas homogeneous methodologies rely mostly on unsolicited waste generation from hydrogen acceptors. Conversely, acceptorless photochemical alkane dehydrogenation in the presence of trans‐Rh(PMe3)2(CO)Cl can be regarded as a more benign and atom efficient alternative. However, this methodology suffers from catalyst deactivation over time. Herein, we provide a detailed investigation of the trans‐Rh(PMe3)2(CO)Cl‐photocatalyzed alkane dehydrogenation using spectroscopic and theoretical investigations. These studies inspired us to utilize CO2 to prevent catalyst deactivation, which leads eventually to improved catalyst turnover numbers in the dehydrogenation of alkanes that include liquid organic hydrogen carriers.